1981
DOI: 10.1126/science.7221561
|View full text |Cite
|
Sign up to set email alerts
|

Chitin: New Facets of Research

Abstract: Research on chitin as a marine resource is pointing to novel applications for this cellulose-like biopolymer. Discovery of nondegrading solvent systems has permitted the spinning of filaments, for example, for use as surgical sutures. New methods for preparing the bioactive alkyl glycoside of N-acetyl-D-glucosamine (the monomer unit of chitin) and a microcrystalline chitin has encouraged their use as promoters for growth of bifidobacteria and as an aid in digestion of high-lactose cheese whey by domestic anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
135
0
9

Year Published

1983
1983
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(146 citation statements)
references
References 14 publications
2
135
0
9
Order By: Relevance
“…In Norwegian aquaculture, astaxanthine has been utilized for a long time to give colour to the flesh of salmonids. Additionally, there may be surprising indirect effects when some chitin is included in the food, an example of which is reported by Austin et al (1981): They found in feeding experiments that chitin at 2 % in the food enhances the development of bifido-bacteria in the intestines of chickens, which in tum synthesize the enzyme lactase. Thus, the lactose in the food mixture becomes digestible and the growth of the chickens is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…In Norwegian aquaculture, astaxanthine has been utilized for a long time to give colour to the flesh of salmonids. Additionally, there may be surprising indirect effects when some chitin is included in the food, an example of which is reported by Austin et al (1981): They found in feeding experiments that chitin at 2 % in the food enhances the development of bifido-bacteria in the intestines of chickens, which in tum synthesize the enzyme lactase. Thus, the lactose in the food mixture becomes digestible and the growth of the chickens is encouraged.…”
Section: Discussionmentioning
confidence: 99%
“…Chitin, a fi-1,4-linked polymer of N-acetylglucosamine, is a major component of the cell wall of many fungi (Austin et al, 1981;Peberdy, 1990). The enzymic degradation of chitin by micro-organisms occurs in two consecutive steps : first the hydrolysis by chitinase [ poly( 1,4-(N-acetyl-fi-~-glucosaminide)) glycanohydrolase; EC 3.2.1.141 to oligomers, mainly dimers, followed by their degradation to free N-acetylglucosamine by chitobiase (N-acetyl-fi-glucosaminidase; EC 3.2.1.30).…”
Section: Introductionmentioning
confidence: 99%
“…Despite their biological interest and potential agronomical usefulness, CHOS with well-defined structures remain poorly accessible. CHOS with 2 to 6 degrees of polymerization (DP) were obtained from chitin by chemical or enzymatic depolymerization or metabolic engineering (2,17,30). Most biological activities require CHOS DP of Ն4 (12), but the synthesis of oligomers with Ն6 DP has been a daunting task.…”
mentioning
confidence: 99%